High-dose atorvastatin versus moderate dose on early vascular protection after ST-elevation myocardial infarction - Gavazzoni M; Gorga E; Derosa G; Maffioli P; Metra M; Raddino R (Dove Medical Press, 2017)
Mara Gavazzoni,1 Elio Gorga,1 Giuseppe Derosa,2–5 Pamela Maffioli,2,4 Marco Metra,1 Riccardo Raddino1 1Cardiology Department, University of Brescia, Spedali Civili di Brescia, Brescia, 2Centre of Diabetes and Metabolic Diseases, Department of Internal Medicine and Therapeutics, University of Pavia, Fondazione IRCCS Policlinico San Matteo, 3Centre for the Study of Endocrine-Metabolic Pathophysiology and Clinical Research, University of Pavia, 4Centre for Prevention, Surveillance, Diagnosis, and Treatment of Rare Diseases, Fondazione IRCCS Policlinico San Matteo, 5Laboratory of Molecular Medicine, University of Pavia, Pavia, Italy Background and aim: Clinical benefits of early high-dose statin therapy after acute coronary syndromes are widely known; however, there is poor evidence on the specific setting of ST-elevation myocardial infarction (STEMI) and dose-dependent effects of this therapy on endothelial function and inflammatory biomarkers in the most vulnerable phase after acute coronary syndromes: the postdischarge period. In our study, we compared the short-term effects of high (80 mg) vs moderate doses of atorvastatin (20 mg) in patients with STEMI undergoing primary percutaneous coronary intervention on endothelial function and vascular inflammation. The aim of our study was the evaluation of dose-dependent short-term effects.Subjects and methods: We enrolled 52 patients within 48 hours of a STEMI to atorvastatin 80 mg (n=26) or 20 mg (n=26). Every patient underwent endothelial function evaluation by the reactive hyperemia–peripheral arterial tonometry (RH-PAT) index on the first day and 1 month after the STEMI. At the same time, we measured lipid profile and serum levels of high-sensitivity CRP, IL6, TNFα, and oxidized LDL.Results: After 1 month of therapy, we observed differences in high-sensitivity CRP levels (0.04±0.02 mg/dL vs 0.36±0.3 mg/dL, P=0.001), IL6 (1.12±0.93 pg/mL vs 3.13±2.84 pg/mL, P=0.03), and improvement in RH-PAT index (1.96±0.16 vs 1.72±0.19, P=0.002) in the group treated with high-dose vs moderate-dose atorvastatin. There was no significant difference in levels of TNFα or oxidized LDL with atorvastatin 20 mg, while there was a reduction in these variables in the group treated with atorvastatin 80 mg. We observed a correlation between high-sensitivity polymerase chain reaction and RH-PAT index on the 30th day after STEMI (r=0.5, P=0.001).Conclusion: Higher dose statin therapy in patients with STEMI undergoing primary percutaneous coronary intervention showed early greater vascular protective effects that moderate dose. Keywords: endothelial dysfunction, endo-PAT, vascular inflammation, acute coronary syndrome